Electron density and temperature measurements, and abundance anomalies in the solar atmosphere - Mohan A.; Dwivedi B.N.; Landi E. (My University, 2025)
Using spectra obtained from the SUMER (Solar Ultraviolet Measurements of Emitted Radiation) spectrograph on the spacecraft SOHO (Solar and Heliospheric Observatory), we investigate the height dependence of electron density, temperature and abundance anomalies in the solar atmosphere. In particular, we present the behaviour of the solar FIP effect (the abundance enhancement of elements with first ionization potential < 10 eV in the corona with respect to photospheric values) with height above an active region observed at the solar limb, with emphasis on the so-called transition region lines.